PENGEMBANGAN BAHAN AJAR BAHASA INDONESIA BERBASIS LINGKUNGAN UNTUK SISWA KELAS 1 SD - HENI LATIFAH (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2021)
This research has the background of the problem of lack of innovation in teaching materials used by teachers, thus causing learning goals to be less optimally reached and students less interested in participating in learning. Elementary school. This research is the development of Indonesian teaching materials starting with a simple form developed in a set of interesting environment-based Indonesian teaching materials. The purpose of this study is to optimize the surrounding environment as a basis for making teaching materials, make environmentally based Indonesian teaching materials for grade 1 elementary school students, and describe the results of the effectiveness of environmentally based Indonesian teaching materials for grade 1 elementary school students. This research uses the type of Research and Development. The data in this study are data about the need for environmentally based Indonesian teaching materials, prototypes of environmentally based Indonesian teaching materials come from observations, interviews, questionnaires and documentation. Data sources were obtained from students and grade 1 teachers at SD 2 Besito, SD 3 Karangmalang, and SD 4 Gondosari. The effectiveness test results showed that the Indonesian language teaching materials were environmentally effective, which was shown by the results at SD 2 Besito at 9,430> 2,03, SD 4 Gondosari at 7,570> 2, and SD 3 Karangmalang at 9,277> 2,04, the t test could be it was concluded t arithmetic> t table then Ho was accepted and environmentally based Indonesian teaching materials were effectively applied.